Convergent-divergent succession of soil microbial communities driven by continuous maize cropping duration via heterogeneous selection processes - Han, Yan-Liang; Yang, Fang-Kun; He, Shu-Ping; Guo, Jia-Cheng; Zou, Yue; Shang, Yun-Xu; Liu, Peng; Wang, Peng-Yang; Wang, Xing; Zhao, Ze-Ying; Wang, Juan; Miao, Chun-Qing (Frontiers in Microbiology, 2025)
The responsive alterations of soil microbial communities driven by continuous maize cropping (CC) and their assembly mechanisms constitute a fundamental scientific question for the sustainability of agricultural ecosystems. However, the assembly processes of microbial communities and their microecological effects under long-term CC remain poorly understood. We hypothesized that maize CC drives predictable shifts in microbial community assembly via increased deterministic selection. To address this, we established a short- to long-term CC gradient (1–25 years). We found that CC significantly altered microbial community structure, the relative abundance of dominant bacterial genera increased with CC years (CCY), whereas dominant fungal genera exhibited a declining trend. Co-occurrence network analysis revealed that long-term CC led to enhanced modularity in bacterial networks and a sharp decline in the proportion of negative correlations. Additionally, our findings reveal a transition from stochastic to heterogeneous selection-dominated processes over time, with microbial diversity metrics showing strong linear relationships with CC duration. This study elucidates how CC shapes convergent-divergent trajectories of microbial communities through heterogeneous selection pressures, providing theoretical support for guiding targeted soil microecological management.